Extended-Spectrum ß-Lactamase-Producing Escherichia coli Among Humans, Beef Cattle, and Abattoir Environments in Nigeria - Aworh, Mabel Kamweli; Ekeng, Eme; Nilsson, Pernille; Egyir, Beverly; Owusu-Nyantakyi, Christian; Hendriksen, Rene S. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Beef cattle, one of the food-producing animals, are linked to humans through a shared environment and the food chain as a major source of animal protein. Antimicrobial drugs are readily accessible for use in food animal production in Nigeria. Beef cattle and abattoir environments harbor pathogenic bacteria such as Escherichia coli (E. coli) which have developed resistance to antimicrobial agents used for prophylaxis or treatment. This study investigated the zoonotic transmission of extended-spectrum beta-lactamase-producing E. coli (ESBL-EC) among humans, beef cattle, and abattoir environments in Abuja and Lagos, Nigeria. Materials and Methods We conducted a cross-sectional study among abattoir workers, beef cattle, and abattoir environments in Abuja and Lagos. Stool, cecal, and environmental samples were collected from apparently healthy workers, slaughtered cattle, and abattoir environments from May to December 2020. Data were collected electronically using open data kit app installed on a mobile phone. Antimicrobial susceptibility patterns were determined using the Kirby–Bauer disk diffusion method against a panel of 16 antimicrobial agents. Phenotypic and genotypic characterizations of the isolates were conducted. Data were analyzed with descriptive statistics. Results From 21.7% (n = 97) of 448 samples, ESBL-EC were isolated and further characterized. Prevalence of ESBL-EC was highest in cattle (45.4%; n = 44), abattoir workers (41.2%; n = 40), and abattoir environment (13.4%; n = 13). Whole-genome sequencing of ESBL-EC showed dissemination of blaCTX-M-15 (90.7%; n = 88); blaCTX-M-14 (5.2%; n = 5); and blaCTX-M-55 (2.1%; n = 2) genes. The blaCTX-M-15 coexisted with blaCTX-M-14 and blaTEM-1 genes in 2.1% (n = 2) and 39.2% (n = 38) of the isolates, respectively. The presence of blaCTX-M-14 and blaCTX-M-15 genes was significantly associated with isolates originating from abattoir workers when compared with beef cattle isolates (p = 0.05; p < 0.01). The most prevalent sequence types (ST) were ST10 (n = 11), ST215 (n = 7), ST4684 (n = 7), and ST2178 (n = 6). ESBL-EC strain (ST205/B1) harbored mcr-1.1 and blaCTX-M15 and was isolated from a worker at Lagos abattoir. In 91 ESBL-EC isolates, 219 mobile genetic elements (MGEs) harbored resistance genes out of which β-lactam genes were carried on 64 different MGEs. Isolates showed equal distribution of insertion sequences and miniature inverted repeats although only a few composite transposons were detected (humans n = 12; cattle n = 9; environment n = 4). Two isolates of human and cattle origin (ST46/A) harboring ESBL genes and carried by MGEs were clonally related. Conclusions This is the first report of blaCTX-M-55 gene in humans and cattle in Nigeria. This study demonstrates the horizontal transfer of ESBL genes possibly by MGEs and buttresses the importance of genomic surveillance. Healthcare workers should be sensitized that people working closely with cattle or in abattoir environments are a high-risk group for fecal carriage of ESBL-EC when compared with the general population.